2015
DOI: 10.1002/app.42262
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of polycarbonate nanocomposites using attapulgite grafted poly(methyl methacrylate) as a potential nanofiller

Abstract: The Core-shell hybrid particles with attapulgite (ATP) as the core and polymethylmethacrylate (PMMA) as the shell (ATP-g-PMMA) were prepared via reversible addition-fragmentation chain transfer (RAFT) polymerization method. The diameter of ATP-g-PMMA was increased to 50-60 nm, and the surface hygroscopicity was decreased observably after surface grafting. Then, ATPg-PMMA hybrid particles were filled into the polycarbonate (PC) by melt mixing to afford nanocomposites, and the mechanical properties, microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Pal has good compatibility with polymer matrices after suitable surface treatments [ 25 , 26 , 27 ]. Pal has been widely used as the polymer enforcement dispersed in polymer matrices [ 28 ]. Chen et al [ 27 ] reported that Pal can significantly reinforce the mechanical properties and thermal stability of PMMA after its surface has been treated with an organic reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Pal has good compatibility with polymer matrices after suitable surface treatments [ 25 , 26 , 27 ]. Pal has been widely used as the polymer enforcement dispersed in polymer matrices [ 28 ]. Chen et al [ 27 ] reported that Pal can significantly reinforce the mechanical properties and thermal stability of PMMA after its surface has been treated with an organic reagent.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic spacings of M-ATP do not change significantly compared to those of ATP. This shows that the crystal structure of M-ATP remains unchanged and the surfactant is only bound to the surface of ATP, without inserting into the nanochannels of the ATP [14,28]. This is similar to the results of Li [11], who used CTAB to modify natural sepiolite and found that the crystal structures of CTAB-modified sepiolite were identical to those As can be seen in Figure 7, the spectra in both a and b showed the characteristic diffraction peaks of the samples at 2θ = 8.4, 29.8, 26.6 and 35.3; these correspond to the (110), (040), (400) and (440) crystal faces of attapulgite, respectively [27].…”
Section: M-atp Characterisationmentioning
confidence: 96%
“…Materials Palygorskite (Pal, 325 mesh) is provided by Anhui Mingmei MinChem Co., Ltd. It was pretreated according to the literature before use (Xu et al, 2015). Dopamine (98%) and tris(hydroxymethyl)aminomethane (99%) were purchased from Shanghai Aladdin Chemical (China).…”
Section: Appendixmentioning
confidence: 99%
“…After treatment, it becomes compatible with many polymer matrices (Liu et al , 2008; Yao et al , 2018; Chen et al , 2011). Therefore, Pal is used extensively as a polymer enforcer in polymer matrices (Xu et al , 2015). Chen et al treated Pal with an organic reagent to obtain an organic–inorganic hybrid (Chen et al , 2011).…”
Section: Introductionmentioning
confidence: 99%